Sexual orientation, gender identity and gender expression-based violence in Catalan universities: qualitative findings from university students and staff - Elena María Gallardo-Nieto; Aitor Gómez; Regina Gairal-Casadó; María del Mar Ramis-Salas (BMC, 2021)
Abstract Background Hate crimes have raised in Spain and the gender and sexuality-based conflicts persist worldwide which leads to this problem having an effect on health and wellbeing. Following a focus of transforming Higher Education Institutions, this research analysed the problem that affects undergraduate students in six Spanish universities. The research goal is to improve the life quality of lesbian, gay, bisexual, transgender, queer and intersex university students, breaking the silence that exists around the violence that this group suffer in Catalonia, Spain. Methods Following the Communicative Methodology, this study has identified violence based on sexual orientation, gender identity or gender expression in the target universities and provided guidelines to improve anti-discrimination protocols. A qualitative method has reached experiences of university students, heads of equality commissions, professors and administrative staff regarding this conflict. Focussing on the qualitative research tools, 30 semi-structured interviews were conducted with university students and staff around issues related to the violence against lesbian, gay, bisexual transgender, queer and intersex students: 1) perception of violence and discrimination, 2) institutional measures, 3) actions against violence. An analysis of exclusionary and transformative dimensions was used to identify emergent themes. Results We have identified two dimensions for the analysis given their impact in contributing or overcoming violence: exclusionary and transformative. A wide range of forms of violence on the grounds of sexual orientation, gender identity and gender expression perpetrated at universities have been identified as exclusionary facts and described by participants in the study. Equality commissions have not received reports of violence based on sexual orientation, gender identity or gender expression, and university staff shows certain unfamiliarity regarding the measures and politics to prevent and intervene in cases of violence against the lesbian, gay, bisexual, transgender, queer and intersex community. Among the results identified as transformative are the ways through which actions of lesbian, gay, bisexual, transgender, queer and intersex groups against violence and the professors' commitment to intervene have a relevant impact on student's wellbeing. An improvement and implementation of anti-discrimination protocols with mandatory applicability has also been documented. Conclusions Findings highlight the need of collecting more evidence that contributes to the improvement of protocols, measures and politics to protect all the members of the university community. A better understanding of violence based on sexual orientation, gender identity and gender expression in HEI's may guide national and international governments to improve the health and well-being of lesbian, gay, bisexual, transgender, queer and intersex persons.